2021
DOI: 10.1021/acsbiomaterials.1c00544
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing Using a Maize Protein: Zein-Based Inks in Biomedical Applications

Abstract: The use of three-dimensional (3D) printing for biomedical applications has expanded exponentially in recent years. However, the current portfolio of 3D printable inks is still limited. For instance, only few protein matrices have been explored as printing/bioprinting materials. Here, we introduce the use of zein, the primary constitutive protein in maize seeds, as a 3D printable material. Zein-based inks were prepared by dissolving commercial zein powder in ethanol with or without polyethylene glycol (PEG400) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 100 publications
1
6
1
Order By: Relevance
“…2 b). Values of yield stresses were found to be superior to previously reported zein gel [ 26 ]. The difference in the preparation method was a possible reason for the superior rheological properties.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…2 b). Values of yield stresses were found to be superior to previously reported zein gel [ 26 ]. The difference in the preparation method was a possible reason for the superior rheological properties.…”
Section: Resultscontrasting
confidence: 62%
“…Our group submitted a patent application for the 3D printing application of zein gel for the first time [ 25 ]. Recently, Tavares-Negrete et al reported zein gel as 3D printing ink that demonstrated slow gelation (21 d) and low yield stress (<30 Pa), and the printed structures exhibited cell adhesion and proliferation properties [ 26 ]. Zein can self-assemble in water because of its hydrophobic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Zein proteins have found wide applications as excipients in the production of inks [ 9 ], adhesives [ 10 ], water resistant paper coating [ 11 , 12 ], plastic-free replacement [ 13 ], encapsulated foods [ 14 ], and a controlled release matrix of active medical components [ 15 , 16 , 17 , 18 ]. Moreover, among various protein sources, zein (the primary storage protein in corn endosperm) has been extensively studied for its capacity to create innovative polymeric films, a feature we want to explore in the future [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial zein in powder form dissolved in ethanol and a plasticizer demonstrated shear thinning properties and hence can be used as a medium suitable for printing. [100,101] A recent study by Ruther et al in 2022 reported 3DP of poly(glycerol sebacate) (PGS)/zein/NaCl inks to produce the scaffold intended for cardiac tissue engineering (as shown in Figure 4a). Improved printability, shape fidelity, and thermal cross-linking could be achieved by adding the protein corn zein and ground NaCl particles with the PGS pre-polymer.…”
Section: Printingmentioning
confidence: 99%